KARAKTERISTIK KARBON AKTIF BERBASIS LIMBAH PELEPAH KELAPA DENGAN VARIASI KONSENTRASI KOH SEBAGAI MATERIAL ELEKTRODA SUPERKAPASITOR - Kimbal, Ariel Javi; Taunaumang, Heindrich; Tumimomor, Farly R.; Rampengan, Alfrie M.; Pawarangan, Ishak (LPPM Politeknik Saint Paul Sorong, 2025)
The current energy needs are increasing due to technological advances and the increasing number of technology users. So, to solve this problem, it is necessary to make major changes and energy renewal by using alternative energy. One of the utilization of alternative energy is energy storage devices such as supercapacitors. In this study, a test was carried out on the activation of coconut stem waste as a supercapacitor electrode with variations in KOH electrolyte, namely 6M, 7M, 8M which produced voltages of 1.254 V, 1.187 V, 1.105 V and produced currents of 87.2 mA, 46.52 mA, 25.38 mA respectively. Based on the results of the study, it showed a decrease in the concentration of electrolytes 6M, 7M, 8M. So it can be concluded that different electrolytes have a significant effect on the voltage and electric current values ​​produced by the supercapacitor electrodes.